DEVELOPING COMPETITION LAW FOR COLLUSION BY AUTONOMOUS ARTIFICIAL AGENTS†. (18th January 2019) - Harrington, Joseph E
Abstract: After arguing that collusion by software programs which choose pricing rules without any human intervention is not a violation of Section 1 of the Sherman Act, the paper offers a path toward making collusion by autonomous artificial agents unlawful.